Religiøse fantomsmerter - Hastrup, Frida (Religionsvidenskabeligt Tidsskrift, 2004)
Religious Phantom Pains - The Khmer Rouge and Victims' historiography This article explores the ways in which biographical accounts by Cambodian refugees in the West portray the oppression during the reign of Pol Pot in the late 1970s. Arguing that victims' biographies constitute a specific genre which is rapidly growing, perhaps due to a general increase in the attention to the voices of the marginalized, the article outlines typical characteristics inherent in this historiographic genre, most notably the claim to representativity and authenticity. Both explicit and implicit religious dimensions can be identified in the Cambodian victims' biographies, and the article examines what this religious content reveals about the handling of the brutality in the Cambodian history. The religious dimension is expressed in both direct references to Buddhist doctrines and ideas and in the indirect truth-claims of the biographies. Invoking Bruce Lincoln's definition of myth as a strategic mode of discourse, possessed of authority and paradignatic truth, the article argues that the biographical accounts of the Cambodian genocide work as mythologies, casting the Khmer Rouge as a cosmological state of emergency, isolated from the Cambodian history at large. The view that the Pol Pot regime is a pathological condition expresses the idea that a functional religious system and the Khmer Rouge regime are mutually exclusive. Thus, religion in the biographies is paradoxically characterised by its absence. In conclusion, it is suggested that this concept of religion poses a more general challenge to sociology of religion regarding the way the analytical object is defined and the relation between text and context.